2016
DOI: 10.1080/01924036.2016.1165712
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of self-legitimacy and audience legitimacy among prison officers in Ghana

Abstract: Criminological research on legitimacy has focused almost exclusively on citizens' normative assessment of legal authorities. However, this line of research neglects power-holders' own assessment of their legitimacy or self-confidence in their moral validity of their claims to power. This paper examines the conditions on which prison officers as power-holders base their legitimacy claims. Data from semi-structured interviews and observation of prison officers in Ghana shows that prison officers in Ghana exude h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 36 publications
(22 reference statements)
1
14
0
1
Order By: Relevance
“…At least since Sparks, Bottoms, and Hay’s (1996) book Prisons and the problem of order , it has been a topic of sustained interest among researchers interested in understanding social order within prisons. Until now, however, work on Self-Legitimacy within criminology had been confined almost exclusively to police studies, with the exceptions of Meško’s work in Slovenia (Hacin et al, 2018; Meško et al, 2017) and Akoensi’s (2016) research in Ghana. The present study addresses this gap in our knowledge by using survey data obtained from prison officers in Ghana.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At least since Sparks, Bottoms, and Hay’s (1996) book Prisons and the problem of order , it has been a topic of sustained interest among researchers interested in understanding social order within prisons. Until now, however, work on Self-Legitimacy within criminology had been confined almost exclusively to police studies, with the exceptions of Meško’s work in Slovenia (Hacin et al, 2018; Meško et al, 2017) and Akoensi’s (2016) research in Ghana. The present study addresses this gap in our knowledge by using survey data obtained from prison officers in Ghana.…”
Section: Discussionmentioning
confidence: 99%
“…In a qualitative study in Ghana, Akoensi (2016) identified relationships between staff and individuals in custody as an important aspect of officers’ Self-Legitimacy. Hacin et al’s (2018) analysis of survey data from Slovenian prison officers found that the more officers believed those in custody held favorable views about them, the more confident of their own legitimacy the officers became (Hacin et al, 2018).…”
Section: Self-legitimacy and Its Correlatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Традиционные модели самолегитимности предполагают, что она зависит от процедурной справедливости, отношений с коллегами, заключенными и законопослушности аудитории [8]. Из-за ограниченного числа исследований самолегитимности в тюремной среде незападных демократических обществ [2] неясно, применимы ли установленные модели ко всем тюремным системам.…”
Section: юридические наукиunclassified